PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) BERBANTUAN BAHAN MANIPULATIF BERPENGARUH TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD GUGUS LETDA KAJENG - ., Ni Putu Lisa Andreyani Patricasari; ., Dra. Ni Wayan Suniasih,S.Pd, M.Pd; ., Drs. I Wayan Wiarta, S.Pd., M.For. (MIMBAR PGSD Undiksha, 2014)
Tujuan penelitian ini adalah untuk mengetahui perbedaan yang signifikan hasil belajar matematika antara kelompok siswa yang dibelajarkan melalui pembelajaran PBI berbantuan bahan manipulatif dengan yang dibelajarkan melalui pembelajaran konvensional siswa kelas V SD Gugus Letda Kajeng Kecamatan Denpasar Utara tahun pelajaran 2013/2014. Jenis penelitian ini merupakan eksperimen semu dengan menggunakan desain penelitian nonequivalent control group design. Populasi penelitian ini adalah seluruh siswa kelas V SD gugus Letda Kajeng Denpasar Utara tahun pelajaran 2013/2014 yang banyaknya 359 orang. Sampel ditentukan dengan random sampling dengan mengacak kelas. Sampel dalam penelitian ini adalah kelas V SD Negeri 14 Pemecutan sebagai kelompok eksperimen dan kelas V SD Negeri 4 Pemecutan sebagai kelompok kontrol dengan jumlah masing-masing kelompok sebanyak 32 orang. Data hasil belajar Matematika dikumpulkan dengan instrumen berupa tes essay berjumlah 10 butir tes yang telah divalidasi. Data hasil belajar matematika dianalisis dengan t-test. Hasil analisis menunjukkan bahwa terdapat perbedaan yang signifikan hasil belajar matematika antara kelompok siswa yang dibelajarkan melalui pembelajaran PBI berbantuan bahan manipulatif dengan yang dibelajarkan melalui pembelajaran konvensional siswa kelas V SD Gugus Letda Kajeng Denpasar Utara tahun pelajaran 2013/2014. Hal tersebut dibuktikan dengan hasil thitung= 4,079 > ttabel (Î± = 0,05, 62) = 2,000. Demikian pula nilai Rerata hasil belajar matematika siswa kelompok eskperimen = 85,625 > = 74,92 rerata hasil belajar matematika siswa kelompok kontrol. Dengan demikian dapat disimpulkan bahwa penerapan pembelajaran Problem Based Instruction (PBI) berbantuan bahan manipulatif berpengaruh terhadap hasil belajar matematika siswa kelas V SD Gugus Letda Kajeng Denpasar Utara tahun ajaran 2013/2014.Kata Kunci : Problem Based Instruction (PBI), Bahan Manipulatif, Hasil belajar matematika The purpose of this study was to find out the significant differences in the outcomes of learning mathematics between students who was studied by using problem based learning Instruction (PBI) assisted manipulative materials with students who was studied by using the conventional learning in class V SD Gugus Letda Kajeng north Denpasar district academic year 2013/2014. This type of research was a quasi-experimental research using non equivalent control group design. The population in this research were all students in the fifth grade of elementary school of SD Gugus Letda Kajeng north Denpasar district academic year 2013/2014, which is the total of students are 359 person. The samples were taken with a random sampling technique to randomize the class. The sample in this study is the class V of SD Negeri 14 Pemecutan as the experimental group and class V of SD Negeri 4 Pemecutan as a control group, which is the total of each group of 32 person. Therefore, The data of Mathematics learning outcomes were collected by instruments in the form of an essay test , which each test consist of 10 items in valid and reliable. The data of Mathematics learning outcomes were analyzed by t - test. The analysis stated that there were the significant differences in the outcomes of learning mathematics between students who was studied by using problem based learning Instruction (PBI) assisted manipulative materials with students who was studied by using the conventional learning in class V SD Gugus Letda Kajeng north Denpasar district academic year 2013/2014. This study was evidenced by the results tcount= 4,079 > ttable (Î± = 0,05, 62) = 2,000, the average value obtained in experimental group learning outcomes ( 85.62 ) is greater than the control class ( 74.92 ). Similarly, average value the outcomes of experimental group learning mathematics = 85.625> = 74.92 average value the outcomes of the control group learning mathematics. However, Based on the result above it can be concluded that the application of problem based learning Instruction (PBI) assisted manipulative materials had an effect in learning mathematics outcomes in class V SD Gugus Letda Kajeng north Denpasar district academic year 2013/2014.keyword : Problem Based Instruction ( PBI ), Manipulative materials, Mathematics learning outcomes